1976
DOI: 10.1007/bf01972212
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant-induced arthritis in four inbred strains of rats. An in vitro study of peripheral T and B lymphocytes

Abstract: The lymphoblastic response (LTT) to non-specific mitogens (PHA, PWM and ConA) of peripheral lymphocytes was investigated at days 0, 7, 14, 21 and 28 after adjuvant injection in four strains of inbred rats: Wistar (WAG), Long Evans (LE), Lewis (LEW) and Brown Norway (BN). LTT was assessed by using 18 hours H3 TdR incorporation in 5 days cultures of whole blood (micromethod). The statistical treatment of data, using principal components multifactorial analysis and analysis of variance showed a striking differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Induction of adjuvant arthritis in Lewis rats by the injection of Mycobacterium butyricum in mineral oil led to an initial increase (on day 4) in the response of the lymph node cells to the T-cell mitogen Con A but not to the B-cell mitogen LPS, as measured by the incorporation of ^H-TdR into cellular DNA. T-cell activation by adjuvants has repeatedly been described [1,27], and peripheral blood lymphocytes with increased responsiveness to Con A have been found in rats with adjuvant arthritis shortly after the induction of the disease [23]. In the present experiments this initial increase in T-cell responsiveness was followed by inhibition of H-TdR incorporation in both Con-A-and LPS-stimulated lymph node cells, 14 days after the induction of the disease.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Induction of adjuvant arthritis in Lewis rats by the injection of Mycobacterium butyricum in mineral oil led to an initial increase (on day 4) in the response of the lymph node cells to the T-cell mitogen Con A but not to the B-cell mitogen LPS, as measured by the incorporation of ^H-TdR into cellular DNA. T-cell activation by adjuvants has repeatedly been described [1,27], and peripheral blood lymphocytes with increased responsiveness to Con A have been found in rats with adjuvant arthritis shortly after the induction of the disease [23]. In the present experiments this initial increase in T-cell responsiveness was followed by inhibition of H-TdR incorporation in both Con-A-and LPS-stimulated lymph node cells, 14 days after the induction of the disease.…”
Section: Discussionsupporting
confidence: 76%
“…Studies with gradient-separated cells showed that the response to Con A of the cell fraction containing T-helper activity (light-density cells [28]) was decreased on day 7 in cultures from untreated and D-penicillamine-treated adjuvant arthritic rats. This decrease was not dependent on the presence of macrophages and may be due to the release of Con-A-responsive lymphocytes into the bloodstream after administration of adjuvant [23]. On day 14 suppressive macrophages were found in cultures of light-density cells from untreated adjuvant arthritic rats but not in the corresponding cultures from Dpenicillamine-treated rats.…”
Section: Discussionmentioning
confidence: 84%
“…1979). Lymph node cells from FCA-treated Wistar rats, which are relatively insensitive to the development of arthritis (Kahan et al, 1976), only stimulated granuloma formation when transferred in large numbers into small sponge implants (Parnham et aZ.). In more recent studies, (Parnham 1980), we found that lymph node cells transferred from Wistar donor rats failed to stimulate granuloma formation when injected into the large sponges used in the present study, even when 108 cells per sponge were transferred.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence for a genetical link to the susceptibility to adjuvant-induced arthritis [Swingle et al, 1969;Rosenthal, 1970;Currey, 1970;Kahan et al, 1976] and EAE [Paterson and Harwin, 1963;Levine and Wenk, 1961;Hughes and Stedronska, 1973] in rats.…”
Section: Discussionmentioning
confidence: 99%